RE-OS ISOTOPE SYSTEMATICS AND PLATINUM GROUP ELEMENT FRACTIONATION DURING MANTLE MELT EXTRACTION: A STUDY OF MASSIF AND XENOLITH PERIDOTITE SUITES - Pearson D.G.; Irvine G.J.; Ionov D.A.; Boyd F.R.; Dreibus G.E. (My University, 2004)
Re–Os isotope and platinum group elements (PGE) systematics are presented for peridotite xenoliths from N. Lesotho (on-craton), S. Namibia (circum-cratonic), the Vitim volcanic field (Baikhal Rift), plus massif peridotites from Beni Bousera, N. Morocco. Mg–Fe variations indicate that these samples have experienced between 5% (Vitim–Beni Bousera) and 50% (Lesotho) melt extraction, providing the opportunity to examine PGE fractionation over a large melting interval. The Namibian xenoliths and Beni Bousera massif peridotites show no variation of iridium group (Ir, Ru, Os; I-PGE) abundances or inter-element fractionations relative to melt depletion indices such as Mg number or Al2O3. Lesotho peridotites show large variations in I-PGE abundances (Os range 0.2–13 ppb) at relatively constant Al2O3 that are not easily rationalised by melt-extraction models. Despite these abundance variations, there is no significant inter-element fractionation of I-PGE, e.g., (Os/Ir)n, showing that these elements are not fractionated by even very large degrees of melting (up to 50% melt extraction). Lesotho peridotites are amongst the most P-PGE (Pt, Pd)-depleted mantle rocks, with highly fractionated chondrite-normalised PGE. PGE systematics for all these peridotite suites allow a relative order of PGE compatibility to be firmly established for mantle melting: